2017
DOI: 10.1051/mmnp/2017073
|View full text |Cite
|
Sign up to set email alerts
|

Stationary solutions of the Vlasov–Poisson system for two-component plasma under an external magnetic field in a half-space

Abstract: We consider the first mixed problem for the Vlasov-Poisson equations with an external magnetic field in a half-space. This problem describes the evolution of the density distributions of ions and electrons in a high temperature plasma with a fixed potential of electric field on a boundary. For a sufficiently large induction of external magnetic field there are constructed stationary solutions supported on some distance from the hyperplane x1 = 0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Since by our general assumption in this section I β λb is a first integral to the Vlasov equation (19) considered with parameter λb, we directly see that f β λ solves the Vlasov equation considered with potential ϕ λ and it remains to check the generalized Poisson equation (7).…”
Section: 2mentioning
confidence: 91%
See 4 more Smart Citations
“…Since by our general assumption in this section I β λb is a first integral to the Vlasov equation (19) considered with parameter λb, we directly see that f β λ solves the Vlasov equation considered with potential ϕ λ and it remains to check the generalized Poisson equation (7).…”
Section: 2mentioning
confidence: 91%
“…In general, stationary solutions of the two-component Vlasov-Poisson equation with trivial potential can be found by relating the cutoff functions ψ + , ψ − on an algebraic level similar to (26). In that case the use of the sub-/supersolution method or a fixed point argument is not needed, see for example [22,35,7]. Moreover, in [7] it has been shown that the trivial potential case allows additional first integrals of the characteristic equations to exist.…”
Section: 3mentioning
confidence: 99%
See 3 more Smart Citations